The perceived salience of vocal emotions is dampened in non-clinical auditory verbal hallucinations. Issue 2 (4th May 2022) - Amorim, Maria; Roberto, Magda S.; Kotz, Sonja A.; Pinheiro, Ana P.
ABSTRACT: Introduction: Auditory verbal hallucinations (AVH) are a cardinal symptom of schizophrenia but are also reported in the general population without need for psychiatric care. Previous evidence suggests that AVH may reflect an imbalance of prior expectation and sensory information, and that altered salience processing is characteristic of both psychotic and non-clinical voice hearers. However, it remains to be shown how such an imbalance affects the categorisation of vocal emotions in perceptual ambiguity. Methods: Neutral and emotional nonverbal vocalisations were morphed along two continua differing in valence (anger; pleasure), each including 11 morphing steps at intervals of 10%. College students ( N  = 234) differing in AVH proneness (measured with the Launay-Slade Hallucination Scale) evaluated the emotional quality of the vocalisations. Results: Increased AVH proneness was associated with more frequent categorisation of ambiguous vocalisations as 'neutral', irrespective of valence. Similarly, the perceptual boundary for emotional classification was shifted by AVH proneness: participants needed more emotional information to categorise a voice as emotional. Conclusions: These findings suggest that emotional salience in vocalisations is dampened as a function of increased AVH proneness. This could be related to changes in the acoustic representations of emotions or reflect top-down expectations of less salient information in the social environment.